Effects of Frying Temperature-Time Combination on Physicochemical, Bioactive Compounds Changes and Storage Life of Vacuum Fried Jackfruit Chips - Chowdhury, M G F; Khan, M H H; Molla, M; Alam, M; Islam, R; Shikder, M F H (South Asian Journal of Agriculture, 2025)
The aim of the study was to optimize the vacuum fried jackfruit chips processing to produce high quality jackfruit chips at suitable frying temperature and time. Jackfruit chips were prepared from matured khaja type jackfruit. The harvested matured jackfruit was cut into halves and separated the bulbs. The seed was removed and bulb was sliced into about 5 mm thickness and then packaged in high density polyethylene (HDPE) packet ( 60 micron) and frozen at -18ºC for 24 - 48 hours. Then the frozen slices were fried instantly using BARI Vacuum Frying Machine at 100,110 and 120ºC for5, 10, 15, 20 and 25 minutes, respectively. The fried chips were de-oiled using BARI De-oiling Machine at 1400 rpm for 3 minutes. Finally, the de-oiled chips were packaged in metalex foil ( 50 micron) packet without nitrogen gas and sealed for storage at ambient temperature (26±2oC, 75±5%RH). Then the changes of physicochemical properties with different frying temperature and time at one-month interval upto six months and consumer preference test was evaluated by expert sensory panelists. According to the sensory panelist, the best frying temperature and time combination was found 110ºC for 25 minutes and 120 ºC for 20 minutes where sensory scored 8.12 and 7.88, respectively. The study will generate the information to the food processors and product development sectors to find out proper ways and means of processing and production of good quality vacuum fried jackfruit chips and thus mitigate the postharvest losses by extending the shelf life and marketability. South Asian J. Agric., Vol. 10, No.1-2, 2024: 36-46